A Retrospective Cohort Study on Rehospitalization following Expanded Criteria Donor Kidney Transplantation. (25th December 2018) - Dunn, Colin; Emeasoba, Emmanuel U.; Hung, Michael; Holtzman, Ari; Bellin, Eran; Greenstein, Stuart
Abstract : Background . Expanded criteria donor (ECD) kidneys are commonly used but are associated with increased graft failure. Graft failure is in turn related to rehospitalization within thirty days post transplant. Our goal was to determine whether ECD kidneys independently lead to rehospitalization within 30 days, 1 year, and 2 years after transplant. Methods . All adult first-time recipients of deceased donor kidneys transplanted from 2003–2012 at our center were reviewed. Models included demographics, medical comorbidities, center for disease control high-risk kidney, ECD kidney, ischemia times, cause of renal failure, immunosuppressive regimen, positive psychiatric screening, alcoholism, surgeon, year the transplant was performed, years on dialysis before transplant, and the number of inpatient hospitalizations within 6 months prior to transplant. We conducted Andersen–Gill modeling and propensity score matching followed by logistic regression. We also used multivariable linear regression to predict average length of stay during rehospitalization. Results . More ECD patients had a rehospitalization at 1 year (70.3% versus 59%, log-rank testp = 0.014 ). Thirty-day and 2-year time marks were not significant. Andersen–Gill models predicting successive hospitalizations yielded HR of 1.42 (p = 0.002 ) and 1.32 (p = 0.015 ) for ECD patients at 1 and 2 years of after transplantation, respectively. Propensity score matching and logistic regression showed a significant relative risk of 1.630 at one year (p = 0.033 ) and 1.313 at two years (p = 0.268 ). There was no significant association between ECD and subsequent lengths of hospital stay. Conclusion . Receiving an ECD kidney is independently associated with multiple readmissions within 2 years of transplant but unrelated to length of stay.